2021
DOI: 10.3390/f12101338
|View full text |Cite
|
Sign up to set email alerts
|

Thermotherapy and Storage Temperature Manipulations Limit the Production of Reactive Oxygen Species in Stored Pedunculate Oak Acorns

Abstract: For many species, seed storage protocols are still being improved to provide viable seeds of the highest quality. Seed storage is extremely problematic for short-lived seeds categorized as recalcitrant, including pedunculate oak (Quercus robur L.), for which the optimal seed storage protocol involves a temperature of –3 °C and 40% acorn moisture content recommendations. The sensitivity of pedunculated oak seeds to temperature manipulations under preparation for long-term storage has been poorly investigated, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
2
5
0
Order By: Relevance
“…Other studies on Quercus spp. confirmed the association of the exposure of acorns to thermotherapy with higher acorn viability, germination rates, and the earlier and more uniform germination [29,30,32,36]. The latter was also noticed in this research (personal observation, data not shown).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Other studies on Quercus spp. confirmed the association of the exposure of acorns to thermotherapy with higher acorn viability, germination rates, and the earlier and more uniform germination [29,30,32,36]. The latter was also noticed in this research (personal observation, data not shown).…”
Section: Discussionsupporting
confidence: 87%
“…Still, thermotherapy is considered to be an efficient method for the control of acorn mycobiota, as the ubiquitous proliferating fungi which can be induced by its application have not yet been proven to reduce the acorn germination after short-term storage [30,33]. Moreover, thermotherapy has been associated with higher acorn viability and germination rates, indicating it does not adversely affect the quality of acorns if combined with the appropriate storage conditions [29,30,33,36]. However, still little is known about the effect of acorn thermotherapy and storage on the characteristics of related seedlings, as there are not many available studies on this topic and most of them are primarily focused on the storage alone [29,[37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…BTO causes strong DNA damage inhibited by antioxidants [67]. Stored acorns display increased ROS levels [21], suggesting that the antioxidant system is less active. Indeed, among the compounds more abundant in seeds stored at −7 • C, the end products of ascorbic acid oxidative metabolism were found (threonic and isothreonic acid) [68].…”
Section: Metabolomic Indicators Of Stressmentioning
confidence: 99%
“…Therefore, depending on the provenance, acorns stored at −7 • C for 3 mo exhibited unchanged or decreased germination capacity [21]. Therefore, this subzero storage temperature (−7 • C) appeared promising for more detailed research in relation to the causes of declined germination capacity and deteriorated seedling establishment because the cold acclimation of pedunculate oak seeds can improve their viability after storage by decreasing reactive oxygen species (ROS) levels [21]. Direct seeding is a major practice for oak forest and woodland establishment, but the influence of basic acorn biology during seed storage is still poorly understood for many oak species [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation